Use of LH or eCG in the last day of superestimulatory treatment - Ereno, R. L. [UNESP]; Rosa, F. S. [UNESP]; Oliveira, A. C S [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP]; Barros, C. M. [UNESP] (My University, 2010)
In the last decades several hormonal treatments to induce multiple ovulation and embryo transfer (MOET) have been developed. Tight control of the time of ovulation allowed the use of fixed-time artificial insemination (FTAI) in embryos donors, facilitating animal management. Although, protocols that allow FTAI have evolved and yield as much embryo as conventional protocols that requires estrus detection, substantial increase in viable embryo production has not been observed in superestimulated bovine cattle. The present mini-review put emphasis on superstimulatory protocols in which the last two doses of pFSH are replaced by eCG or LH. Recent results indicate that an extra LH stimulus (using eCG or LH), on the last day of P-36 superestimulatory treatment, seems to improve transferable embryo yield in both Bos taurus and Bos indicus cattle.
Keywords: Bovine; ECG; Embryo transfer; FSH; LH; Superovulation; Animalia; Bos; Bos indicus; Bos taurus; Bovinae